2014
DOI: 10.4236/psych.2014.510129
|View full text |Cite
|
Sign up to set email alerts
|

Family Structure and Psychological Health in Young Adults

Abstract: This study explored the effect of the gendered structure of siblings in intact and non-intact families, on family relations, social support, perceived control, and psychological distress in a sample of 708 young adults (294 males and 414 females) aged between 18-21 years. Of the sample 96 were singletons, 208 had both a brother and sister, 206 had a brother and no sister, and 198 had a sister and no brother. While the results show that both the gender of the participants and the gender of the sibling seem to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In essence the findings support the suggestion that the presence of a female sibling in the family is related to more positive outcomes in terms of mental health (Cassidy, Wright & Noon, 2014). The direction of main effects from Anova analysis shows that participants of both sexes who had a female sibling had better mental health than those who did not whether this was in a situation of having only a sister or having both a sister and brother.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In essence the findings support the suggestion that the presence of a female sibling in the family is related to more positive outcomes in terms of mental health (Cassidy, Wright & Noon, 2014). The direction of main effects from Anova analysis shows that participants of both sexes who had a female sibling had better mental health than those who did not whether this was in a situation of having only a sister or having both a sister and brother.…”
Section: Discussionsupporting
confidence: 71%
“…There is evidence that males are associated with more conflict and lower levels of cohesion in sibling relations (Weiss, Schitaffino & Ilowite, 2001). Similarly, there is some evidence that families with female siblings tend to be related to more expressive family environments and that this may, in turn, impact on coping and health (Cassidy, Wright & Noon, 2014). It is well recognised that the combination of high levels of conflict and less cohesive family emotional environments are associated with more negativity in sibling relationships (Milevsky, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Some study results pointed that the gender structure of siblings affects mental health. Cassidy et al reported that those having a brother experienced the most psychological distress [51]. The most psychologically distressed were boys who have brothers; the second most distressed were girls with brothers, closely followed by both boys and girls with both brothers and sisters.…”
Section: Relationship With Siblingsmentioning
confidence: 99%
“…Moreover, young people report receiving higher levels of support from mothers than from fathers, and mothers tend to be perceived as having a more supportive role than fathers (e.g., Umaña-Taylor et al, 2012;Zupancic et al, 2012;Mendonca and Fontaine, 2013;Galambos et al, 2018). Young people also report experiencing greater closeness, support, and warmth in their relationships with sisters than with brothers (e.g., Finzi-Dottan and Cohen, 2011;Cassidy et al, 2014;Tibbetts and Scharfe, 2015). Finally, studies with grandparents have shown that maternal grandmothers provide the highest levels of emotional support for young people (Wise, 2008;Gray et al, 2019).…”
Section: Sex or Gender Differencesmentioning
confidence: 99%